1980
DOI: 10.1080/03079458008418402
|View full text |Cite
|
Sign up to set email alerts
|

Natural and experimental nodular dermatomycosis in chickens

Abstract: The occurrence of unusual cases of generalised, tumour-like cutaneous swellings in 2-3-month-old chickens, from which A. flavus or C. albicans could be isolated, is described. Histologically similar but clinically different lesions could be produced experimentally in 1-month-old chickens by intradermal inoculation of A. flavus alone or combined with C. albicans. The latter organism alone failed, however, to produce the cutaneous lesions by the same route of inoculation. Intracardiac inoculation of A. flavus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Following our observations of A. flavus, which infects layered chickens and has shown no respiratory signs or lesions, we hypothesized that the infection occurred through contaminated food but not through the respiratory passage, and then fungal organisms are expected to spread in the different organs of the infected bird. These results also are in agreement with Barton Previous studies have shown that A. flavus was isolated from natural infections including the skin [37]. The data obtained from our study showed grayish-white skin nodules on the brisket and subcutaneous haemorrhage associated with dumpiness and immune suppression.…”
Section: Discussionsupporting
confidence: 93%
“…Following our observations of A. flavus, which infects layered chickens and has shown no respiratory signs or lesions, we hypothesized that the infection occurred through contaminated food but not through the respiratory passage, and then fungal organisms are expected to spread in the different organs of the infected bird. These results also are in agreement with Barton Previous studies have shown that A. flavus was isolated from natural infections including the skin [37]. The data obtained from our study showed grayish-white skin nodules on the brisket and subcutaneous haemorrhage associated with dumpiness and immune suppression.…”
Section: Discussionsupporting
confidence: 93%
“…Chute et al [19] described a systemic fatal infection by Aspergillus fumigatus in White Rock cockerels, that was attributed to the contamination of the cutaneous incision performed to caponize the animals. Finally, in a case of some chickens, cutaneous aspergillosis was seen with generalized, tumor-like swellings, the infection being limited to the skin [20]. …”
Section: Discussionmentioning
confidence: 99%
“…In birds, skin granulomas are generally associated with bacterial, parasitic, or fungal infections. 5,13,17 Cases of avian mycobacteriosis are rare in wild birds; in psittacines, the disease is manifested by swellings around the head and neck. 13,16 Although some cases of contact dermatitis have been described in close association with feather follicles, such lesions are usually located on the plantar surface of the footpads and toes (pododermatitis) of broilers, turkeys, and Anseriformes.…”
mentioning
confidence: 99%